EFFECTIVE WAYS OF LEARNING FOREIGN LANGUAGES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article talks about the easy and effective ways of learning foreign languages, which are of great importance today, and through them, the formation of listening comprehension, fluency, writing and speaking skills.